2020
DOI: 10.2147/clep.s273853
|View full text |Cite
|
Sign up to set email alerts
|

<p>Performance of ICD-10-CM Diagnosis Codes for Identifying Acute Ischemic Stroke in a National Health Insurance Claims Database</p>

Abstract: The validity of the International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) coding for the identification of acute ischemic stroke (AIS) in Taiwan's National Health Insurance claims database has not been investigated. This study aimed to construct and validate the case definition algorithms for AIS based on ICD-10-CM diagnostic codes. Patients and Methods: This study identified all hospitalizations with ICD-10-CM code of I63* in any position of the discharge diagnoses from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 20 publications
2
55
0
Order By: Relevance
“…The study findings were similar to our previous study that examined the performance of ICD-10-CM codes for identifying AIS in Taiwan's NHI claims database. 16 Nevertheless, discussing the potential implications for researchers interested in hemorrhagic stroke using this claims database is worthwhile. In contrast to AIS, acute hemorrhagic stroke mainly encompasses SAH (I60) and ICH (I61).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study findings were similar to our previous study that examined the performance of ICD-10-CM codes for identifying AIS in Taiwan's NHI claims database. 16 Nevertheless, discussing the potential implications for researchers interested in hemorrhagic stroke using this claims database is worthwhile. In contrast to AIS, acute hemorrhagic stroke mainly encompasses SAH (I60) and ICH (I61).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study on ICD coding for AIS reported a similar finding, which may be explained by the higher prevalence of comorbidities among the elderly. 16 Compared to young adults, elderly subjects carry a higher risk of hemorrhagic transformation of AIS, 22,23 and a higher risk of brain tumor. 24 Furthermore, elderly people are naturally more likely to have chronic or remote hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that there is good concordance between ICD coding and clinical diagnosis in other neurologic conditions, like stroke. 40 More specifically, the use of diagnostic coding for this purpose has been used in previous FMD research, 15,16,41 while also being an accepted strategy for analyzing big datasets of nonneurological diagnoses. 42,43 We attempted to counter the issue of diagnostic accuracy by including only patients with at least one neurology encounter and by examining a subgroup of patients who had a diagnosis of ICD-10 F44-related diagnosis code expressly associated with an outpatient neurology evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Use of ICD codes to establish a diagnosis is common to the emerging study of large, retrospective datasets. There is evidence to suggest that there is good concordance between ICD coding and clinical diagnosis in other neurologic conditions, like stroke 40 . More specifically, the use of diagnostic coding for this purpose has been used in previous FMD research, 15,16,41 while also being an accepted strategy for analyzing big datasets of non‐neurological diagnoses 42,43 .…”
Section: Discussionmentioning
confidence: 99%
“…The accuracy of ICD-9-CM diagnostic codes in Taiwan's NHIRD was verified in previous studies [21][22][23] . Although ICD-10-CM was used in Taiwan for only a few years, there also have been studies validating the diagnostic codes between ICD-9-CM and ICD-10-CM in NHIRD 24,25) . All these study results indicated that records from NHIRD are accurate and consistent between ICD-9-CM and ICD-10-CM.…”
Section: Data Sourcementioning
confidence: 99%